PHYTOCHEMICAL SCREENING ANO IN VITRO ANTIOXIDANT ACTIVITY OF PASS/FLORA EDULIS SIMS (PASSION FRUIT) - Rojas A., J. (2010)
The objectives of this study were to determine the main groups of secondary metabolites in the ethanol extract of the leaves and the fruit juice of Passiflora edulis, and in vitro antioxidant activity of methanol extract of the leaves. The phytochemical screening was done following the usual techniques of chemistry; and for antioxidant activity using 1,1-diphenyl-2-picryl-hidrazil (DPPH) and four sample concentrations: 200, 100, 50 and 10 ).µg 1 ml, the absorbance was measured at a wavelength of 517 nm. We calculated the concentration of the extract caused a 50% decrease in absorbance of the solution of OPPH (IC 50). We found in leaves and fruit juice the presence of tannins, flavonoids, saponins, coumarins, quinones and alkaloids. Antioxidant capacity was observed dose-dependent, so an IC50 = 124 mg 1 ml. lt is concluded that the diverse secondary metabolites are found in both leaves and fruit, highlighting the greater amount of flavonoids in the fruit juice, on the other hand, the methanol extract of the leaves was effective antioxidant in vitro.